Leadership New Insights - Franco, Mário (IntechOpen, 2022)
Leadership is viewed as a phenomenon allowing advantages for organizations and their success. Although much research has been done on the concept of leadership, many studies do not include the different styles, perspectives, and contexts of leadership. As such, this book aims to fill this gap by combining several studies on leadership from different perspectives. The various chapters address such topics as millennial leaders, Theory X style leadership, leadership in the turbulent environment, emotional intelligence, and much more. This volume shows how new insights about leadership can stimulate organizational development in various countries and regions worldwide.